Саадачні трійники-розподільники золотоординського часу - Осипенко, М.С. (Археологія, 2017)
У статті розглядається питання функціонального застосування трійників-розподільників золотоординського часу, а також вводиться в науковий обіг раніше не опублікований матеріал із зібрань Національного музею історії України. Здійснена спроба систематизації розподільників на основі їхньої орнаментації та складена карта поширення аналогічних знахідок. The existence of the Mongolian bowcase belts is difficult to trace in the course of archaeological excavations at sites, but they are known from the depictions on mediaeval miniatures. Being dressed over the armour and the main military belt, such equipment served as a modern load bearing system, did not hamper the movement, and opened a quick access to a bow. A special scheme for belts’ division was provided by tees. The tees-distributors kept in the funds of the National Museum of Ukrainian History which have not been studied before are taken into scientific investigation. They can be attributed to the period of the Mongolians’ presence in the Steppes of South Rus. Also, the previously published findings are systematized, there infiltration and usage on the territory of Ukraine are traced. Наличие саадачных поясов у монголов трудно проследить в ходе археологических работ на памятниках, но они известны за изображениями средневековых миниатюр. Такая портупея выполняла функции современной разгрузочной системы, одевалась поверх доспеха и основного боевого пояса, не сковывала в движении и открывала быстрый доступ к дистанционному оружию. Особенную схему распределения ремней обеспечивали тройники. Статья вводит в научный оборот тройники-распределители, что хранятся в фондах Национального музея истории Украины и могут быть отнесены к периоду монгольского присутствия в южнорусских степях. Также проводится систематизация уже опубликованных изделий, прослеживается их проникновение и бытование на территории Украины.